Autonomous or controlled interpreters? Model of Werktreue internalization for classical musicians - Fujimoto, Marie; Uesaka, Yuri (Frontiers in Psychology, 2024)
Self-regulated learning―a cyclical process in which a learner sets a goal, monitors, and self-reflects on one’s learning to set the next goal―is vital in instrumental learning. However, many conservatory students fail to initiate self-regulated learning; as a result, they take lessons passively, practice ineffectively, and fail to give satisfactory performance. These learning experiences could harm students’ well-being, and physical and mental health problems are widespread among students. Nevertheless, factors contributing to self-regulated learning remain unknown. We hypothesized that musicians’ autonomy in musical interpretation, which we refer to as interpretive autonomy, plays a pivotal role in self-regulated learning. Without developing interpretation, musicians fail to set personal goals, monitor, and self-evaluate their performances in terms of musicality. Although previous studies imply that interpretation plays a significant role in self-regulated learning, this has not been clearly demonstrated. Studies on interpretive autonomy are scarce due to a complicated discourse surrounding performers’ freedom in interpretation. The ideology of Werktreue underpins the classical music field, and classical music performances are evaluated based on how faithfully a performer interpreted the composer’s intention. Yet musicians hold various beliefs regarding the meaning of faithful interpretation, thus the degree of interpretive autonomy cannot be assessed unless its clear definition is provided. In addition, the mechanisms that promote or hinder interpretive autonomy in learning remain unexplained. To address these issues, we proposed a model of Werktreue internalization by applying self-determination theory. The model defines interpretive autonomy based on internalization types, identifies its effects on musicians’ learning behavior and well-being, and reveals the mechanisms that promote or hinder interpretive autonomy in learning experiences. This model allows researchers and educators to assess the degree of interpretive autonomy, attribute impaired learning behavior and well-being to a lack of interpretive autonomy, and promote interpretive autonomy by supporting students’ psychological needs in interpretation.